Workers in Perpetuity? : Notes about the mrt Workers of the Egyptian Middle Kingdom Based on the Stela CG 20516 - Rosell, Pablo Martín (2018)
This paper aims to study a social group of Egyptian people called mrt workers, based on their representation in epigraphic, funerary and literary sources dating to the Middle Kingdom. The stela CG 20516 is especially important for our research since it shows one of the few iconographic representations of these mrt workers. This stela is essential since it shows the mrt workers performing their tasks and serving their deceased owner in an exceptional way. Such representation suggests a personal link in perpetuity between these workers and their masters. Therefore, the mrt workers' social and legal status is reconsidered by studying whether they were forced to work periodically or were dependent workers in perpetuity.